Collaborative Governance in Service Innovation: A Study of Dukcapil with the Religious Court in the Integrated Marriage Legalization Service Program in Raja Ampat - Ivana Beatrice Manpioper; Amirul Mustofa; Sedarmayanti Sedarmayanti; Dian Ferriswara (International Forum of Researchers and Lecturers, 2026)
This study aims to analyze the practice of collaborative governance in the innovation of population administration services through the integrated marriage legalization (isbat nikah) program implemented by the Civil Registration and Population Office (Dukcapil) in collaboration with the Religious Court. The program represents a governmental initiative to provide legal certainty for unregistered marriages while improving citizens’ access to legal identity documents. This research employs a qualitative approach with descriptive analysis to examine inter-organizational collaboration in public service delivery. The analytical framework refers to the collaborative governance model developed by Chris Ansell and Alison Gash, focusing on three key dimensions: starting conditions, institutional design, and facilitative leadership. The findings indicate that the initial conditions of collaboration were driven by the high number of unregistered marriages and the institutional limitations of each agency in addressing the issue independently. In terms of institutional design, the collaboration is supported by formal cooperation agreements, clear division of roles, and integrated service mechanisms among participating institutions. Furthermore, facilitative leadership plays a crucial role in fostering coordination, communication, and shared commitment among stakeholders. The study concludes that collaborative governance in the integrated marriage legalization service program enhances the effectiveness of population administration services while providing legal certainty for citizens.